The Monastic Landscape of Adiabene in the First Centuries of Islam - Novacek, Karel; Wood, Philip (Journal of Islamic Archaeology, 2020)
The article considers the archaeological and literary evidence for Christian populations in provinceof Hadyab (Adiabene) in northern Iraq in the 5th to 9th centuries AD. We argue that there was a conspicuous expansion of settlements, both rural and urban, clustered around newly built churches, monasteries and fortifications in the 7th century. We link this to local Christian aristocrats (shahregan), who flourished under the light tax regime of the Early Caliphate and are discussed in contemporary Syriac hagiography.